2012
DOI: 10.1128/jvi.01012-12
|View full text |Cite
|
Sign up to set email alerts
|

Negative Elongation Factor-Mediated Suppression of RNA Polymerase II Elongation of Kaposi's Sarcoma-Associated Herpesvirus Lytic Gene Expression

Abstract: Genome-wide chromatin immunoprecipitation assays indicate that the promoter-proximal pausing of RNA polymerase II (RNAPII) is an important postinitiation step for gene regulation. During latent infection, the majority of Kaposi's sarcoma-associated herpesvirus (KSHV) genes is silenced via repressive histone marks on their promoters. Despite the absence of their expression during latency, however, several lytic promoters are enriched with activating histone marks, suggesting that mechanisms other than heterochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 73 publications
3
48
0
Order By: Relevance
“…1). It was recently shown that the HDACi nBA can stimulate transcriptional elongation of RNA polymerase II, which is prepoised on the PAN promoter during latency (61). This effect was independent of Rta expression and the production of mature virus.…”
Section: Discussionmentioning
confidence: 98%
“…1). It was recently shown that the HDACi nBA can stimulate transcriptional elongation of RNA polymerase II, which is prepoised on the PAN promoter during latency (61). This effect was independent of Rta expression and the production of mature virus.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, it is possible that pausing occurs during viral transcription but the paused Pol II is released quickly and therefore is not captured by Pol II ChIP-seq. The roles of DSIF and NELF in transcription of HSV-1 genes have not been reported, although these factors help control the transcription of other herpesviruses (Kaposi's sarcoma-associated herpesvirus [KSHV] and EpsteinBarr virus [EBV] [50,51]). …”
Section: Discussionmentioning
confidence: 99%
“…9). Since this effect was observed in iSLK cells infected with Rta null virus, in which Rta expression is induced by Dox from an ectopic cassette carried in the cellular genome (42,43), it proves that Pin1 does indeed interact with Rta protein posttranslationally in infected cells, rather than solely induce Rta expression during reactivation. We showed that Pin1 cooperated with Rta to transactivate DE genes (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A doxycycline (Dox)-inducible Rta cell line TREx BCBL-1-Rta (a gift of J. Jung, University of Southern California [USC] [38]), a wild-type, KSHV-infected B lymphoma cell line BCBL-1, and uninfected B lymphoma cell line BL-41 were maintained in RPMI 1640 supplemented with 12% fetal bovine serum (Sigma) as previously described (15,22 Vieira), were maintained as previously described (15,22,(39)(40)(41)(42)(43)(44). iSLK cell lines contain Dox-inducible Rta and were gifts of D. Ganem (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation